The Role of Disease Activity as a Determinant of Central Sensitivity and Body Awareness in Fibromyalgia Patients: A Cross-Sectional Study - Yasemin Mirza; Adem Küçük (Ahi Evran Medical Journal)
Purpose: The present study aimed to identify the influence of disease activity on central sensitization (CS) and body awareness in fibromyalgia syndrome (FMS) patients.